ANALYSIS OF THE IMPLEMENTATION OF P5 LOCAL WISDOM THEME THROUGH TRADITIONAL COMPETITIONS IN ELEMENTARY AGE CHILDREN (PIONIR: JURNAL PENDIDIKAN, 2025)
The aim of this research is to instill values. Pancasila, in the field for elementary age children at MIN 11 Ngawi, through a traditional competitions to commemorate the 79th Independence Day of the Republic of Indonesia at the Kenteng Sine Ngawi Independence Field. Qualitative research method with a descriptive approach. Research subjects were educators, Phase B students and parents. The data collection method uses triangulation through observation, interviews and documentation. Theme P5 of this research is Local Wisdom through Traditional Competitions. The research results show that in implementing P5 there are various stages, starting from planning, including the organizing team, school readiness, determining the theme, identifying traditional competitions, preparing activity plans, implementation and reflection. The implementation stage includes introduction to traditional competitions, delivery of material and discussions, traditional competition practice and reflection. The final stage or evaluation of P5 activities builds cultural awareness, teaches cultural values, evaluates competitions and inspires students. Through traditional competitions, children have made a real contribution, apart from gaining new knowledge and insight, they are also able to regenerate a sense of love for the nation's culture in this era of rapid globalization.Keywords: Independent Curriculum, Traditional Competition